The Influence of Verbal and Non-Verbal Communication on the Interest of Watching Subscribers Youtube Channel Majelis Lucu Indonesia Abstrack - Ginting, Hansel C. Putra TR; Pohan , Syafruddin; Nurbani (Indonesian Journal of Advanced Research, 2024)
The purpose of this study was to analyze the influence of verbal and non-verbal communication on the interest of subscribers of the YouTube channel Indonesian Funny Council (MLI). Researchers use descriptive methods with quantitative approaches. The results of the study showed that the variables of verbal communication have an influence on the interest of subscribers of the Youtube channel Indonesian Funny Council (MLI), the variables of non-verbal communication have an influence on the interest of subscribers of the YouTube channel Indonesian Funny Council (MLI), the variables of verbal communication and non-verbal communication influence on the interest of subscribers of the Youtube channel Indonesian Funny Council (MLI) simultaneously, the variables of verbal and non-verbal communication simultaneously have an effect of 76.8% on interest Watch subscribers of Youtube channel Indonesian Funny Council (MLI). The remaining 23.2% were influenced by other factors, such as age and gender.